Knowledge mapping and research trends of IL-33 from 2004 to 2022: a bibliometric analysis - Jin, Jingyi; Wan, Yantong; Shu, Qiang; Liu, Jinghua; Lai, Dengming (Frontiers in Immunology, 2023)
Background: IL-33 has been an active research area recently. However, there is a lack of a comprehensive and systematic bibliometric analysis of IL-33. The present study aims to explore the hot spots and trends in this field through bibliometric analysis and visualization. Methods: The publications related to IL-33 were identified and selected from the Web of Science Core Collection (WoSCC) database on 7 December 2022. We examined the downloaded data with bibliometric package in R software. Our study used CiteSpace and VOSviewer to conduct bibliometric and knowledge mapping analysis regarding IL-33. Results: From 1 January 2004 to 7 December 2022, we identified 4711 articles on IL-33 research published in 1009 academic journals by 24652 authors in 483 institutions from 89 countries. The number of articles had grown steadily over this period. The United States of America(USA) and China contribute the most significant number of publications, and the USA maintains a dominant position in this field. The University of Tokyo and the University of Glasgow are the most active institutions. The most prolific journal is Frontiers in Immunology, while the Journal of Immunity is the top 1 co-cited journal. Mckenzie, Andrew N. J. has the most significant number of articles, and Jochen Schmitz is co-cited most. The major fields of these publications are immunology, cell biology, and biochemistry & molecular biology. After analysis, the high-frequency keywords of IL-33 research relate to molecular biology (sST2, IL-1, etc.), immunological effects (type 2 immunity, Th2 cells, etc.), and diseases (asthma, cancer, cardiovascular diseases, etc.). Among these, the involvement of IL-33 in the regulation of type 2 inflammation has strong research potential and is a current research hotspot. Conclusion: The present study quantifies and identifies the current research status and trends of IL-33 using bibliometric and knowledge mapping analysis. This study points to the direction of research for scholars in IL-33-related research.